EFFECTIVE STRATEGIES FOR INCREASING STUDENT MOTIVATION IN ENGLISH LANGUAGE TEACHING - Rahmatjonov Muhammadiy Bahodirjon o’g’li; Ashurali Mirzayev Baxtiyor o'g’li (TADQIQOTLAR, 2026)
Abstract Student motivation is one of the most significant factors influencing success in English language learning. Motivated students demonstrate higher levels of engagement, persistence, and academic achievement. This article examines effective strategies for increasing student motivation in English language teaching. It explores the concept of motivation, the teacher’s role, and practical classroom strategies, including communicative activities, technology integration, learner autonomy, assessment practices, and social support. The findings suggest that motivation is dynamic and can be enhanced through purposeful and student-centered teaching approaches.